2006
DOI: 10.1111/j.1365-2648.2006.03806.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experiences of students with dyslexia

Abstract: The clinical setting provides a challenging environment for nursing students with dyslexia, who find personalized ways to manage their disability. A dyslexia diagnosis continues to carry a stigma that may result in non-disclosure, with implications for the level of support available. Greater awareness of the practice-specific needs of such students is required to ensure appropriate support and public safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
66
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(128 citation statements)
references
References 16 publications
6
66
0
2
Order By: Relevance
“…As a potentially stigmatising condition, this is an important area. Studies of nursing students have explored this area and found disturbing results -for example, that students felt stigmatised and unwanted on clinical placements (Morris andTurnbull, 2006, Child andLangford, 2011). Whilst there are no similar published studies of medical students, this does correspond with our own findings on the experiences of UK junior doctors (Shaw & Anderson, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…As a potentially stigmatising condition, this is an important area. Studies of nursing students have explored this area and found disturbing results -for example, that students felt stigmatised and unwanted on clinical placements (Morris andTurnbull, 2006, Child andLangford, 2011). Whilst there are no similar published studies of medical students, this does correspond with our own findings on the experiences of UK junior doctors (Shaw & Anderson, 2017).…”
Section: Discussionsupporting
confidence: 70%
“…People with conditions that affect their appearance, such as psoriasis or excess hair, report low self-confidence and avoid social situations because of anticipation of negative social reactions [28,29]. People who stutter [30,31] or have dyslexia [32][33][34] also often fear and avoid social situations which may expose their difficulties and report anxiety and low self-esteem, and damage to career prospects. As in DP, people with dyslexia report that confirmation that their difficulties are due to a neurological condition can help to alleviate the sense of personal failure [33].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, people who stutter can reduce the strain of social encounters by disclosing their difficulties in advance [31]. However, like those with DP, people with dyslexia felt that disclosure could have negative consequences and were concerned that a diagnosis could evoke stigmatising stereotypes of mental deficiency [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blankfield (2001) reported negative experiences of students who disclosed that they were Dyslexic while on work placements. Morris and Turnbull (2006), in interviewing 18 nursing students, also found 6 students had not disclosed their Dyslexia because of reticence in doing so. However, in the case of DSA there is obviously a balance of gains and losses in disclosing.…”
Section: The Implications Of Disclosure and Developmental Disordersmentioning
confidence: 99%